Structural Damage Information Fusion Based on Soft Computing. (4th September 2012) - He, Haoxiang; Yan, Weiming; Zhang, Ailin
Abstract : The significance of information fusion for structural health monitoring and damage detection is introduced. The three levels of information fusion for multisensors are described. For the complex in the structural health monitoring, the distributed multisensor information fusion is more suitable and the structure is discussed. In the damage information fusion for character level, the concept for structural integral support vector machine damage detection matrix, damage self-information, and damage information entropy are presented. For a complex structure, it can be divided into multiple substructures in order to simplify the difficult for health monitoring, the data acquisition and support vector machine are established for each substructure in order to form integral damage detection matrix. In the damage information fusion for decision level, the methods based on fuzzy set theory, material element theory, and fuzzy neural network are proposed. The results given by a numerical example about space structure show that all the methods are valid and effective.